Okay across languages: toward a comparative approach to its use in talk-in-interaction - Betz, Emma; Deppermann, Arnulf; Mondada, Lorenza; Sorjonen, Marja-Leena (Studies in language and social interaction, 2021)
"OKAY has been termed a 'spectacular expression' and 'America's greatest invention.' This volume offers an in-depth empirical study of the uses that have resulted from its global spread. Focusing on actions and interactional practices, it investigates OKAY in a variety of settings in 13 languages. The collected work showcases the importance of a holistic analysis: Prosodic realization and the placement of OKAY in its larger sequential and multimodal context emerge as constitutive for distinct uses in individual languages. An inductive approach makes it possible to identify practices not previously documented, for example OKAY used for 'qualified acceptance' or as a 'continuer', and to document a core of recurrent, similar uses across languages. This work also outlines new research directions for comparative analysis by offering first insights into the diachronic development of OKAY's uses and the relationship of OKAY to other particles in specific languages"--
Includes bibliographical references and index
This book took shape during two inspiring workshops held in Mannheim and Helsinki in 2017. (Acknowledgements)
Keywords: Konferenzschrift -- 2017 -- Mannheim; Konferenzschrift -- 2017 -- Helsinki; Kontrastive Pragmatik; Kontrastive Semantik; Kontrastive Syntax; O.K.